2020
DOI: 10.2355/isijinternational.isijint-2019-796
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Activity Coefficient of Solute in Infinite Dilute Liquid Iron Based on Surface Tension of Binary Liquid Fe Alloys

Abstract: Expansion of the system for thermodynamic parameters in liquid iron is expected for the improvement in iron & steelmaking processes. The development of their calculation method is one of the issues for its realization. In the present work, we proposed a calculation method for an activity coefficient of solute in infinite dilute liquid iron to element i, γ ο i , based on the surface tension of binary liquid Fe alloys. It was found that the estimated values by our proposed method agree with recommended literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The surface tension of the melt depends on the chemical composition and structure of the surface layer. Copper and silicon in iron reduce the surface tension [17], niobium increases, and the effect of boron is ambiguous and depends on its content [18]. All alloying elements in the Fe73.5Cu1Nb3Si13.5B9 alloy tend to diffuse to the iron surface [19,20].…”
Section: Resultsmentioning
confidence: 99%
“…The surface tension of the melt depends on the chemical composition and structure of the surface layer. Copper and silicon in iron reduce the surface tension [17], niobium increases, and the effect of boron is ambiguous and depends on its content [18]. All alloying elements in the Fe73.5Cu1Nb3Si13.5B9 alloy tend to diffuse to the iron surface [19,20].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is important to study the surface tension of Fe-Mn-C melts in the context of possible structural transitions in a liquid and crystallization conditions. The surface tension of Fe-Mn-C melts was studied earlier [14][15][16][17][18][19][20][21][22][23][24]. It was found that there was no excess molar volume of Fe-(3-10) wt % Mn, and the experimental values of surface tension agreed with those calculated by the Butler formula [14].…”
mentioning
confidence: 78%
“…The effect of Mn additions on the surface tension of liquid iron was reported in [18]. The activity coefficients of Mn in an infinitely dilute Fe solution were calculated using the Butler formula [20]. The adsorption of Mn on the surface of Fe-Mn melts was studied [21].…”
mentioning
confidence: 99%